Tinjauan Filosofis Hubungan antara Pendidikan, Moral dan Agama - Victor Imaduddin Ahmad; Sudarto Murtaufiq (Akademika, 2021)
This article aims at discussing the relationship between morality and religion, and what the contribution of these two fields to education. They are are important instruments to be included in the curriculum. Moral education and religious education are specific forms of education, which are needed to realize a complete education. It does not mean that they will become the overall goal of education. Moral education teaches students the knowledge of what to do regarding behavior that affects their well-being or happiness and that of others, including an understanding of the reasons behind such moral behavior.